Pelatihan Model Pembelajaran Langsung Sebagai Aplikasi CTL untuk Guru IPA SMP di Ogan Ilir - Riyanto Riyanto; Mgs M. Tibrani; Safira Permata Dewi; Ermayanti Ermayanti; Yenny Anwar; Meilinda Meilinda; Susy Amizera; Elvira Destiansari; Nike Anggraini (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
The results of an interview with a science teacher in Ogan Ilir district that science teachers mastered the skills of various learning models including direct learning models. Some of the junior high school science materials are declarative or procedural. Material that is declarative or procedural requires skills that are carried out in stages of the entire series of activities displayed. The purpose of this community service activity (CSA) is to improve the ability of junior high school science teachers to master the direct teaching model, compile a direct teaching model rpp and be able to implement the direct teaching model in the classroom. The implementation of the activity is carried out in several stages, namely: 1. The preparatory stage, namely field observations and interviews with teachers, reading references to direct learning model materials, holding discussions with PPM team members, preparing training materials in the form of Power Point, approaching school staff and teachers and coordinating related parties. 2. Implementation stage, namely direct training with training methods, demonstrations and discussions and visualizations. Through CSA activities, science teachers from the Ogan Ilir MGMP groups can compile or modify direct learning models with a scientific approach. MGMP science teachers have been able to make 5 aspects of learning implementation planning (LIP), namely listing: learning indicators and objectives, organizing materials, media and learning resources, learning activity steps, and evaluating learning outcomes. Therefore, the RPP format made by mgmp science teachers in Ogan Ilir district was declared feasible. This is evident from the assessment results with all 100 values. After attending the CSA training material, participants enjoyed the material presented, felt that this material was very necessary and felt that their knowledge increased